Tutor Support and Motivation in EFL Learning: A Conceptual Overview - Seirra Ammara Nur Rabbani; Seful Bahri (Universitas Islam Negeri Palopo, 2026)
Even after years of formal instruction, many EFL learners find it difficult to build confidence and fluency in speaking. Issues like the excessive number of students in a classroom, lack of teaching time and inadequate one-to-one attention frequently become barriers to good learning. This leads to a high number of learners resorting to non-formal learning settings, including individual tutoring and English classes, which are more personalized and flexible. Nonetheless, the role of tutor support in learner motivation and the effects of tutor-learner interaction on the learning process have received little research. The objective of the present study is to determine how tutor support helps to improve the motivation of learners based on three major motivational theories: Self-Determination Theory (SDT), the Socio-Educational Model (SEM), and Expectancy-Value Theory (EVT). This paper uses a conceptual research design to synthesize the existing literature to investigate how these theories can explain the motivational processes in non-formal EFL settings. The results suggest that tutors are important in promoting the motivation of learners by helping them feel autonomy, competence, and relatedness, developing positive attitudes towards the target language, and improving expectations towards success and perceived value of the tasks by learners. In this regard, tutors not only give linguistic knowledge but also act as motivational facilitators, emotional supporter and cultural mediators.